A Pandangan Teologi Penderitaan Paulus terhadap Adversity Quotient - Wijiati, Wahyu; Nugraheni, Tia Ariana (Student Evangelical Journal Aiming At Theological Interpretation, 2025)
The life of a believer is characterized by a willingness to suffer for Christ, where adversity quotient (AQ), the intelligence to endure hardship, plays a crucial role in sustaining faith under pressure. This study aims to explore the implications of the Apostle Paul’s theology of suffering for the development of AQ among believers. Employing a descriptive qualitative method through literature review, the research examines Paul's theology of suffering and its relevance to AQ. The findings reveal that Paul’s ability to endure suffering was rooted in his unwavering faith in Jesus Christ, which significantly strengthened his AQ. The study concludes that understanding Paul's theology of suffering provides a solid foundation for developing spiritual and emotional resilience in believers. This research is expected to enhance both theological insight and practical application for enduring and growing through life’s adversities